HUBUNGAN ANTARA OPTIMISME DAN SELF-ESTEEM PADA MAHASISWA PROGRAM DIPLOMA III KEBIDANAN - Musthofawi, Asiah (Asosiasi Pendidikan Kebidanan Indonesia, 2019)
This research was conducted to investigate the correlation between optimism and self-esteem in midwifery college students, diploma III program. Sample from this study are midwifery college students, diploma III program who are in the region DKI Jakarta, West Java, Banten and West Sumatera. Overall, 571 midwefery student was participated in this research by filling out the questionnaire optimism and self-esteem. Optimism was measured by Life Orientation Test-Revised (LOT-R) constructed by Scheier, Carver dan Bridges (1994), while self-esteem was measured by Rosenberg’s Self-esteem Scale (RSE) constructed by Rosenberg (1965). The result show that there is a significant positive relationship between optimism and self-esteem (r = 0.378, p = 0.000). Implication of this study is, the result can be considered in designing an intervention program, in order to increase candidates midwife’s internal quality in Indonesia.